Extinct bird exhibit - Tinney, Jack (Philadelphia Evening Bulletin, 1978)
"John DiMeo, 7, of Bristol, gets a close look at the extinct bird, the Great Auk, on a visit to the Academy of Natural Sciences." With clipping